Encyclopedia of multimedia technology and networking - Pagani, Margherita (Hershey, PA : Idea Group Reference, 2005)
"This encyclopedia offers a comprehensive knowledge of multimedia information technology from an economic and technological perspective"--Provided by publisher
Includes bibliographical references and index
1 10
Keywords: Multimedia communications -- Encyclopedias